Isolation, engineering and ecology of temperate phages from the human gut - Sofia Dahlman; Laura Avellaneda-Franco; Emily L. Rutten; Emily L. Gulliver; Sean Solari; Michelle Chonwerawong; Ciaren Kett; Dinesh Subedi; Remy B. Young; Nathan Campbell; Jodee A. Gould; Jasmine D. Bell; et al. (Nature, 2025)
Abstract Large-scale metagenomic and data-mining efforts have revealed an expansive diversity of bacteriophages (phages) within the human gut 1–3 . However, functional understanding of phage–host interactions within this complex environment is limited, largely due to a lack of cultured isolates available for experimental validation. Here we characterize 134 inducible prophages originating from 252 human gut bacterial isolates using 10 different induction conditions to expand the experimentally validated temperate phage–host pairs originating from the human gut. Importantly, only 18% of computationally predicted prophages could be induced in pure cultures. Moreover, we construct a 78-member synthetic microbiome that, when co-cultured in the presence of human colonic cells (Caco2), led to the induction of 35% phage species. Using cultured isolates, we demonstrate that human host-associated cellular products may act as induction agents, providing a possible link between gastrointestinal cell lysis and temperate phage populations 4,5 . We provide key insights into prophage diversity and genetics, including a genetic pathway for domestication, finding that polylysogeny was common and resulted in coordinated prophage induction, and that differential induction can be influenced by divergent prophage integration sites. More broadly, our study highlights the importance of culture-based techniques, alongside experimental validation, genomics and computational prediction, to understand the biology and function of temperate phages in the human gut microbiome. These culture-based approaches will enable applications across synthetic biology, biotechnology and microbiome fields.